The aqueous and crystalline forms of L-alanine zwitterion - Degtyarenko, I.; Jalkanen, Karl; Gurtovenko, A.; Nieminen, R. (American Scientific Publishers, 2008)
The structural properties of L-alanine amino acid in aqueous solution and in crystalline phase have been studied by means of density-functional electronic-structure and molecular dynamics simulations. The solvated zwitterionic structure of L-alanine (+NH3-C2H4-COO-) was systematically compared to the structure of its zwitterionic crystalline analogue acquired from both computer simulations and experiments. It turns out that the structural properties of an alanine molecule in aqueous solution can differ significantly from those in crystalline phase, these differences being mainly attributed to hydrogen bonding interactions. In particular, we found that the largest difference between the two alanine forms can be seen for the orientation and bond lengths of the carboxylate (COO-) group: in aqueous solutionthe C-O bond lengths appear to strongly correlate with the number of water molecules which form hydrogen bonds with the COO- group. Furthermore, the hydrogen bond lengths are shorter and the hydrogen bond angles are larger for L-alanine in water as compared to crystal. Overall, our findings strongly suggest that the generally accepted approach of extending the structural information acquired from crystallographic data to a L-alanine molecule in aqueous solution should be used with caution.